Changes in the Core Kinship Terminologies: A Case Study of Hindu Kinship Terms in Kerala - Resmi P (Language in India, 2018)
Kinship terminologies are considered to be that part of the core vocabulary resistant to linguistic changes. Dravidian language Malayalam, hAa classificatory set of kinship terminologies in which the terms for the secondary kin, i.e., father’s brother or mother’s sister is a derivative of the term for father and mother respectively. The goal of the present paper is to examine the changing patterns in the native Hindu kinship terms in the in Kerala. In the contemporary urban social organisation the generic terms in English which is generally used for addressing relations not related by blood ‘uncle’ and ‘aunt-ie’ seem to have started replacing the native kinship terms. Undoubtedly, this change in the use of kinship terminology is not a case of internal linguistic changes. The kinship terms are not just a string of letters which constitute a lexicon, but encapsulate expressions of human relationships, how these relationships are organised, how they interact with one another, the roles they play. They are the true indicators of how the kin roles are enacted and maintained. It implies that the kinship terms cannot be abstracted from actual living experiences and entails that when there are transformations in the nature of relationships in a family or in society in wider context, the semantic content of the kinship terminologies starts shrinking, and consequently in course of time, they are replaced or lost. Any transformation in the use of kinship terminology essentially indicates transformations in the very nature of these family relationships it embodies